Analisis Sosial Ekonomi Masyarakat Kelurahan Petuk Katimpun dalam Mendukung Pemanfaatan Danau Hanjalutung Sebagai Kawasan Alternatif Pengembangan Usaha Perikanan di Kota Palangka Raya - Nyata Susila (Fakultas Peternakan Universitas Kristen Palangka Raya, 2012)
The increasing fish production through continuous fishing effort has not always been able to survive due to the pressure on water resources in the future more and more powerful, so if the fishing is done with attention to conservation norms, would adversely affect the sustainability of aquatic resources. To solve these problems, the city government of Palangka Raya took a policy to utilize existing lakes in the area of alternatives to the development of aquaculture. Hanjalutung lake is one of the lakes located in watersheds Rungan river own ends and is one of public waters is considerable potential for local communities as a source of fishing effort. The purpose of this study is to investigate and analyze of the social condition of communities, as well as level of profitability of fishing communities around the lake. Methods of analysis of the social conditions of community around the lake is obtained by using a questionaire and analyzed descriptively, and economic aspect is analyzed by looking at the benefits of fishing communities. The results of the observations on the social aspects, that the average age of the population most productive age (38,5 years), level of formal education among primary school graduation (53,34%) by the number of members in an average family of 4-5 people (48,33%). The result of the analysis of fishing effort is still profitable.